2017
DOI: 10.2169/internalmedicine.8214-16
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib-induced Rectal Perforation with Abscess

Abstract: An 86-year-old Japanese man was diagnosed with stage IV lung adenocarcinoma. The patient was treated with crizotinib after echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase (ALK) rearrangement was detected from his pleural effusion. He subsequently developed abdominal pain and rebound tenderness in the right lower abdomen. Contrast-enhanced abdominal CT showed a low-density area in the abdominal cavity. The size of the abscess was decreased by drainage and the administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In particular, alectinib is an anaplastic lymphoma kinase (ALK) inhibitor used in patients with nonsmallcell lung cancer, harbouring ALK rearrangements. Even if ALK inhibitors have been associated with various adverse effects, such as visual disturbances, nausea and vomiting (8), to the best of our knowledge our patient represents the second case of PI associated to alectinib administration described in literature (9).…”
Section: S Brocchi Et Almentioning
confidence: 83%
“…In particular, alectinib is an anaplastic lymphoma kinase (ALK) inhibitor used in patients with nonsmallcell lung cancer, harbouring ALK rearrangements. Even if ALK inhibitors have been associated with various adverse effects, such as visual disturbances, nausea and vomiting (8), to the best of our knowledge our patient represents the second case of PI associated to alectinib administration described in literature (9).…”
Section: S Brocchi Et Almentioning
confidence: 83%
“…Our analysis found a significant signal for rectal perforation with crizotinib, but not with the other ALK inhibitors. Yanagisawa et al 13 reported a case of a 86-year-old male with stage IV lung adenocarcinoma who developed rectal perforation associated with crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Yanagisawa et al. 13 reported a case of a 86-year-old male with stage IV lung adenocarcinoma who developed rectal perforation associated with crizotinib.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations